Perancangan Motion Graphic Pola Makan Ibu Hamil Sebagai Bahan Sosialisasi Stunting Desa Jambearjo - Erina Rahmanil Mauludiyah; Eva Handriyantini; Rina Nurfitri (Jurnal Desain Komunikasi Visual Asia, 2022)
The danger of stunting is currently something that must be considered, prevention that is carried out by socializing it to the public using appropriate media is the right way to support the effectiveness during the socialization. The problem occurs because the media used in the socialization is less precise so that with the new media based on motion graphics, the expectation is it will be able to make the socialization work effectively and achieve the target audience. To overcome the problem, a new solution is needed. It is in the new form of media based on motion graphics which has function later on as the materials in the new socialization and education that can be accessed by the public through social media. The role of the media is to simplify the introduction and the prevention of stunting both directly (offline) and indirectly (online). Keywords: Stunting, Motion Graphic, Socialization, Education